Diseño de un banco de condensadores para la corrección del factor de potencia de la empresa Banchisfoof S.A. - LLumiquinga Loya, Fredy Santiago (2012)
In the present project a capacitors bank for correcting the electric power factor of the BANCHISFOOD S.A. Company is designed through a technical and economic analysis; and the selection of the type of bank to be used according to the electrical characteristics of the company is made. The basic concepts of the main electrical parameters: active power, reactive power, power factor; which serve to better understand the advantages obtained when performing the power factor correction, are shown. The technical and economic benefits of having an electric power factor greater than 0.92 are also determined. Electrical data of the parts and areas that make up the company are obtained, through the load Analyzer; furthermore electricity bills are analyzed and are used for the economic and technical design of the capacitors bank. Data collection of electrical system